"Atribuição inequívoca dos sinais de RMN e da estereoquímica relativa de compostos rígidos tipo 'gaiola' (cage-like) : estudo experimental e teórico" - Salles, Roberta Chechetto (2009)
In this work the Nuclear Magnetic Ressonance (NMR) technique was used for the unequivocal attribution of the 1H and 13C{1H} NMR signals from one-dimensional (1H NMR, 13C NMR and DEPT-135) and bidimensional (COSY, HMBC, HSQC and NOESY) experiments. The six analyzed compounds were tricyclo[6.2.1.02,7]undeca-4,9-diene-3,6-dione (3), tricyclo[6.2.1.02,7]undec-9-eno-3,6-dione (20), rel- (6S)-6-hidroxytricyclo[6.2.1.02,7]undec-9-en-3-one (21), rel-(1R, 6S, 7R, 2S, 8S)-3-Oxo-6-(3,4,5-trimethoxyfenilcarbonnyloxi)tricyclo[6.2.1.02,7]undec-9-ene (22), rel-(1S, 2S, 6S, 8S, 7R, 9R)-6,9-epoxytricyclo[6.2.1.02,7]undecan-3-one (23), rel- (2S, 4S, 6S, 10S, 1R, 9R)-10-bromine-6,9-epoxitricyclo[6.2.1.02,7]undecan-3-one (24) were obtained from the adduct obtained from the Diels-Alder reaction between cyclopentadiene and p-benzoquinone. This study focused on cage-like compounds which are known for being biologically active, being amantadine the first and most known bioactive cage-like compound. All chemical shift values were attributed despite the difficulty found due to signals overlapping. When possible, the spin-spin coupling constants (J) were also attributed. The distinction between the bridge hydrogens, for the majority of the compounds, was done by the analysis of the 2D NOESY NMR spectrum. The data obtained from the experimental attribution of the 1H and 13C NMR chemical shift and spin-spin coupling values (J) were compared with theoretical data obtained from computational calculations. The mean deviation (MD), standard deviation (SD) and the linear correlation coefficient (R) values were analyzed for the endo and exo adducts in order to evaluate if the B3LYP/cc-pVTZ model presented good results in shielding tensors (d) and spin-spin coupling constants (J) calculations. Analyzing the results obtained from the theoretical calculations it was observed that, for the chemical shift values the model used presented good results, however, for the calculations of the coupling constants the model did not present satisfactory results